MARKETING MIX STRATEGY TO INCREASE MICROFINANCE DISTRIBUTION AT PT PERMODALAN NASIONAL MADANI INDRAMAYU - Irmana (UTSAHA: Journal of Entrepreneurship, 2023)
Marketing strategies will be effective if supported by the right marketing mix strategy. One of the business units of PT Permodalan Nasional Madani Indramayu is required to contribute by achieving branch income in accordance with the predetermined target. Revenue optimization can be achieved by maximizing the distribution of financing to ultra-micro, micro and small businesses. This research aims to determine the effect of marketing mix (product, price, place, promotion, people, physical evidence, and process) on the decision to become a microfinance customer at PT Permodalan Nasional Madani Indramayu so that the right marketing mix strategy can be determined to increase the distribution of microfinance at the company. This research is quantitative with a correlational approach. In addition, the sampling technique used in this research is slovin technique. Research uses 2 variables. The dependent variable used the customer’s decision, while the independent variable, that is, the variable that is used as the cause of changes or that affects the dependent variable, is the marketing mix which includes product, physical evidence, people, process, promotion, place, and price.